Transforming Islamic Religious Education: Evidence of Smart TV Effectiveness in Enhancing Student Motivation - Novi Nur Sa`diyah; Faizal Baehaqi; Alief Buddiyono (Papanda Publisher, 2026)
The Fourth Industrial Revolution demands digital transformation in education, yet Islamic Religious Education (IRE) in rural elementary schools continues to rely on conventional pedagogies that diminish student motivation. This study examines Smart TV effectiveness as an interactive learning medium in enhancing IRE learning motivation within rural contexts. A mixed-methods sequential explanatory design was employed at SD Negeri 2 Windunegara, Banyumas Regency, involving 93 students, one IRE teacher, and the principal. Quantitative data were collected using an ARCS-based motivation questionnaire (α = 0.85-0.89) administered pre- and post-implementation, while qualitative data were gathered through classroom observations, semi-structured interviews, and documentary analysis over three months. Smart TV implementation produced statistically significant improvements across all ARCS dimensions: Attention (d = 2.17), Relevance (d = 1.89), Confidence (d = 2.30), and Satisfaction (d = 2.13), all p < .001. Three pedagogical patterns emerged—immersive presentation, participatory simulation, and collaborative construction—transforming passive learning into interactive engagement. Previously reticent students demonstrated increased participation, and unexpected intergenerational knowledge transfer occurred. Findings validate Keller's ARCS model and Mayer's multimedia learning theory in Indonesian Islamic education contexts, demonstrating that theoretically grounded technology integration can transform traditional religious education when supported by adequate infrastructure and committed leadership. The study contributes empirical evidence for rural school digitalization policy while acknowledging limitations in generalizability and implementation duration.